Efecto antimicrobiano de piper nubigenum kunth, frente a cepas atcc de enterococcus faecalis y candida albicans productoras de enfermedades bucales - Estefania Katherine, Mosquera Santos (2021)
ABSTRACT: Ancestral medicine is an inexpensive and easily acquired alternative that naturally helps disease treatment. The research aims to evaluate the antimicrobial effect of Piper nubigenum Kunth against ATCC strains of E. faecalis and C. albicans that produce oral diseases. Ethereal, alcoholic, and aqueous extracts were obtained by maceration, then a phytochemical analysis was carried out to obtain secondary metabolites; the extracts were concentrated and divided into concentrations of 100%, 75%, 50%, 25%, it applied on different antibiogram blank disks(OXOID), in addition to 1 positive control disc in the E. faecalis strain (Amoxicillin + clavulanic acid) and the C. albicans strain (Ketoconazole), in addition, a negative control disc (distilled water), for each strain. It was established that the ethereal extracts, in all their concentrations and 25% alcoholic, compared to strains of E. faecalis, obtained the highest values among the extracts in general. Regarding the extracts in general against strains of C. albicans, the values range between 2.33 mm and 7.66 mm. In conclusion, the secondary metabolites correlate with the results obtained in the inhibitory halos, showing more inhibition in the ethereal extracts in all their concentrations and 25% alcoholic compared to ATCC strains of E. faecalis, while the extracts in general compared to the ATCC strain of C. albicans did not produce significant results, with null values according to the Duraffourd scale (p = 0.00; p = 0.742; p = 0.002; p = 0.002; p = 0.001).